Body roll in swimming: A review - Psycharakis, S. G.; Sanders, R. H. (Journal of Sports Sciences, 2010)
In this article, we present a critical review of the swimming literature on body roll, for the purposes of summarizing and highlighting existing knowledge, identifying the gaps and limitations, and stimulating further research. The main research findings can be summarized as follows: swimmers roll their shoulders significantly more than their hips; swimmers increase hip roll but maintain shoulder roll when fatigued; faster swimmers roll their shoulders less than slower swimmers during a 200-m swim; roll asymmetries, temporal differences in shoulder roll and hip roll, and shoulder roll side dominance exist in front crawl swimming, but there is no evidence to suggest that they affect swimming performance; and buoyancy contributes strongly to generating body roll in front crawl swimming. Based on and stimulated by current knowledge, future research should focus on the following areas: calculation of body roll for female swimmers and for backstroke swimming; differences in body roll between breathing and non-breathing cycles; causes of body roll asymmetries and their relation to motor laterality; body roll analysis across a wide range of velocities and swimming distances; exploration of the association between body roll and the magnitude and direction of propulsive/resistive forces developed during the stroke cycle; and the influence of kicking actions on the generation of body roll.